2017
DOI: 10.1186/s12263-017-0560-8
|View full text |Cite
|
Sign up to set email alerts
|

Folate deficiency as predisposing factor for childhood leukaemia: a review of the literature

Abstract: BackgroundFolic acid and its derivates, known as folates, are chemoprotective micronutrients of great interest because of their essential role in the maintenance of health and genomic integrity. The supplementation of folic acid during pregnancy has long been known to reduce the risk of neural tube defects (NTDs) in the foetus. Folate metabolism can be altered by many factors, including adequate intake through diet. Folate deficiency can compromise the synthesis, repair and methylation of DNA, with deleterious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 180 publications
(181 reference statements)
0
25
0
3
Order By: Relevance
“…Bifidobacterium contributes significantly to de novo biosynthesis of folate in gut and to folate store in colon [ 31 ]. Humans cannot synthesize folate and are dependent on external sources (from food or bacterial synthesis), and the deficiency of folate can result in chromosomal instability [ 32 , 33 ] and susceptibility for childhood leukemia [ 34 ]. Reduced levels of Bifidobacterium could result in decreased folate levels in the large intestine and thus increase the risk of aneuploidies associated with rectal neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…Bifidobacterium contributes significantly to de novo biosynthesis of folate in gut and to folate store in colon [ 31 ]. Humans cannot synthesize folate and are dependent on external sources (from food or bacterial synthesis), and the deficiency of folate can result in chromosomal instability [ 32 , 33 ] and susceptibility for childhood leukemia [ 34 ]. Reduced levels of Bifidobacterium could result in decreased folate levels in the large intestine and thus increase the risk of aneuploidies associated with rectal neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…The possible risk factors for the onset and progression of CBSCT have been examined in many studies, however the etiology continues to be largely unknown [55,56]. Several studies have recently suggested a potential protective effect of folic acid on certain pediatric cancers [53,57,58], while only a minority of studies investigated the effects of maternal folate intake on CBSCT [29][30][31][32][33][34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…‱ Maternal folic acid supplementation before and during pregnancy protects against the risk of childhood leukemia in the offspring…”
Section: Introductionmentioning
confidence: 99%